The Durability of Stone Matrix Asphalt (SMA) Mixtures Designed Using Reclaimed Asphalt Pavement (RAP) Aggregates Against Floodwater Immersion - Edi Yusuf Adiman; Mardani Sebayang; Ermiyati Ermiyati; Yenita Morena (Journal of Applied Engineering and Technological Science (JAETS), 2023)
The durability of asphalt mixtures against floodwater immersion can serve as a reference to anticipate potential road damage. Moreover, Reclaimed Asphalt Pavement (RAP) materials have been discovered as a substitute for aggregate materials in road pavement due to their environmental friendliness and cost-effectiveness. Therefore, this research aimed to assess the durability of asphalt mixtures produced using RAP aggregate materials against floodwater immersion for 1, 2, 4, and 8 days. The process involved using Stone Matrix Asphalt (SMA) mixtures with a proportion of 33% RAP aggregate as test specimens. The Marshall test conducted on the asphalt mixture produced an optimum asphalt content (OAC) value of 6.1%. Moreover, the durability of the mixture reduced up to the 8th day of immersion with a residual strength value of 86.29%. It was also discovered that the reduction in the durability value of the mixture produced using 33% RAP aggregate was almost similar to the application of 100% new aggregate (non-RAP). This means RAP aggregate materials are feasible as an environmentally friendly substitute in the mixture of road pavement.